Exploring the Nurses Experiences During Unprecedented Crisis: A Heideggerian Perspectives - Ai Ling, Chen; Rekaya Vincent, Balang (Universiti Putra Malaysia, 2025)
Introduction:Nurses face numerous experiences, challenges, and responsibilities throughout their careers. Nurses, as agents of change, occupy a unique position in shaping historical reflections, policies, and processes for navigating current and future pandemics. This study aimed to explore the nurse’s experiences during and after an unprecedented crisis particularly during the COVID-19 pandemic. Materials and Methods: This qualitative study employed interpretive phenomenology to provide an in-depth exploration of nurses' lived experiences. Data were collected through semi-structured interviews and analysed using thematic analysis. Results: The experiences were examined through Van Manen’s four structures: lived body, lived time, lived space, and lived other. Nurses reported significant physical strain, including fatigue from long shifts and the continuous use of personal protective equipment (PPE). Their perception of time became distorted, with workdays blending into personal time, heightening anxiety. Social distancing and isolation protocols disrupted family relationships, leading to loneliness and emotional distance. Teamwork was vital but strained due to stress and burnout, with occasional conflicts arising. Post-pandemic, nurses are likely to experience long-term physical and psychological impacts. Conclusion: The findings of this study precede the need for systemic changes in healthcare, including better recognition, empowerment, and a supportive work environment. Nursing education should include resilience, teamwork, and crisis management training. Additionally, mental health support systems must be prioritized to address the long-term effects of crises on nurses’ well-being.